1982
DOI: 10.1288/00005537-198204000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinus hypoplasia and superior orbital fissure asymmetry

Abstract: Misdiagnosis of maxillary sinus hypophasia usually as sinus infection, sometimes as neoplasm, can lead to unnecessary and difficult surgical explorations. Associated anatomical abnormalities, e.g., caudal displacement of the ipsilateral frontal lobe of the brain or central position in the maxilla of the infraorbital nerve may create unexpected surgical hazards. Associated orbital enlargement can lead to diagnostic confusion in the investigation of headache, especially if the superior orbital fissures show mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…9 Maxillary sinus hypoplasia is reported in 1.7 to 10.4% of patients with sinonasal symptoms. 10,11 To the best of our knowledge, this is the third case report of total paranasal sinus aplasia in the English language literature and the first ever case reported in India. While dealing with paranasal sinus disease, paranasal sinus aplasia and hypoplasia should be kept in mind because: First, the prevalence of frontal and sphenoidal sinus aplasia or hypoplasia have been shown to be higher in patients with cystic fibrosis or primary ciliary dyskinesia.…”
Section: Discussionmentioning
confidence: 74%
“…9 Maxillary sinus hypoplasia is reported in 1.7 to 10.4% of patients with sinonasal symptoms. 10,11 To the best of our knowledge, this is the third case report of total paranasal sinus aplasia in the English language literature and the first ever case reported in India. While dealing with paranasal sinus disease, paranasal sinus aplasia and hypoplasia should be kept in mind because: First, the prevalence of frontal and sphenoidal sinus aplasia or hypoplasia have been shown to be higher in patients with cystic fibrosis or primary ciliary dyskinesia.…”
Section: Discussionmentioning
confidence: 74%
“…There is some variability in the reported incidence of unilateral MSH. In contrast to Karmody et al 8 who reported a 1.73% incidence, Bassiouny et al 2 reported a 3.6% and a recent study by Bolger et al 3 reported 10.4%. This could be attributed to the different methods of diagnosing MSH.…”
Section: Discussionmentioning
confidence: 77%
“…Karmody et al 8 defined the criteria for a small sinus based on assessment of the pneumatization of the zygomatic process (lateral extent), and pneumatization of the alveolar process (inferior extent). Two additional criteria were used by Bassiouny et al 2 These included failure of the sinus to develop cephalad toward the orbit leaving the inferior orbital wall in its original curved (concave upward) position, with the infraorbital foramen near the center of the maxilla, and diminished expansion of the sinus medially toward the nasal cavity with resulting lateral displacement of the nasal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computed tomography (CT) is now the best measure for imaging the sinuses [7], and clinically significant ethmoid disease may be present with relatively minimal plain radiological findings that would be quite evident on CT scan [8][9][10].…”
Section: Mms Taher Os Haddad Ct Scan Findings Of Occult Sinus Pathomentioning
confidence: 99%